Engaging primary care physicians in system change – an interpretive qualitative study in a remote and rural health region in Northern British Columbia, Canada. Issue 5 (28th May 2019) - Snadden, David; Reay, Trish; Hanlon, Neil; MacLeod, Martha
Abstract : Objectives: To describe how physicians were engaged in primary healthcare system change in a remote and rural Canadian health authority. Design: A qualitative interpretive study based on a hermeneutic approach. Methods: 34 transcribed in-depth interviews with physicians and administrators relevant to physician engagement were purposively sampled from a larger data set of 239 interviews gathered over a 3-year period from seven communities engaged in primary healthcare transformation. Interviews were coded and analysed interpretively to develop common themes. Setting: This research is part of a larger study, Partnering for Change I, which investigated the efforts of Northern Health, a rural regional health authority in British Columbia, to transform its healthcare system to one grounded in primary care with a focus on interdisciplinary teams. It reports how physician engagement was accomplished during the first 3 years of the study. Participants: Interviews with 34 individuals with direct involvement and experience in the processes of physician engagement. These included 10 physicians, three Regional Executives, 18 Primary Healthcare coordinators and three Division of Family Practice leads. Results: Three major interconnected themes that depicted the process of engagement were identified: working through tensions constructively, drawing on structures for engagement and facilitating relationships. Conclusions: Physician engagement was recognised as a priority by Northern Health in its efforts to create system change. This was facilitated by the creation of Divisions of Family Practice that provided a structure for dialogue and facilitated a common voice for physicians. Divisions helped to build trust between various groups through allowing constructive conversations to surface and deal with tensions. Local context mattered. Flexibility in working from local priorities was a critical part of developing relationships that facilitated the design and implementation of system reform.